Spatial Reasoning of Middle School Students in View of Mathematics Anxiety - Fitriyani, Harina; Kusumah, Yaya Sukjaya; Dahlan, Jarnawi Afgani; Hendroanto, Aan (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
The low spatial reasoning ability and high mathematics anxiety of junior high school students is an interesting discussion to be studied in more depth to understand students' spatial reasoning abilities and mathematical anxiety. Therefore, this study aims to explore the spatial reasoning abilities of junior high school students in solving geometric problems in terms of students' math anxiety. The research method used is qualitative research with a case study type. Data were collected through written tests to explore spatial reasoning data, followed by task-based unstructured interviews and a Likert scale questionnaire to explore math anxiety data. Furthermore, the research data were analyzed by following the Miles and Huberman model, which consisted of data reduction (data reduction), data presentation (data display), and concluding (verification). The results showed that the average student's math anxiety was 2.294. Students' spatial reasoning abilities were dominated at a moderate level, namely 69.23%. The results also show that the students' spatial reasoning ability does not depend on the math anxiety category. The ability of spatial orientation is the ability most students master. Once the mathematical anxiety and spatial reasoning abilities of students are understood, it is intended that the teacher would take this into account while structuring geometry instruction in the classroom, which will foster the growth of students' spatial reasoning while simultaneously lowering the number of students' mathematical anxiety.Rendahnya kemampuan penalaran spasial dan tingginya kecemasan matematika siswa SMP menjadi bahasan menarik untuk dikaji lebih mendalam supaya diperoleh pemahaman menyeluruh tentang kemampuan penalaran spasial dan kecemasan matematika siswa. Oleh karena itu penelitian ini bertujuan untuk mengeksplorasi kemampuan penalaran spasial siswa SMP dalam memecahkan masalah geometri ditinjau dari kecemasan matematika siswa. Adapun metode penelitian yang dilakukan adalah penelitian kualitatif dengan jenis studi kasus. Data dikumpulkan melalui tes tertulis untuk menggali data penalaran spasial dilanjutkan dengan wawancara tidak terstruktur berbasis tugas, dan angket skala likert untuk menggali data kecemasan matematika. Selanjutnya data penelitian dianalisis dengan mengikuti model Miles dan Huberman yang terdiri atas: reduksi data (data reduction), penyajian data (data display), dan penarikan kesimpulan (verification). Hasil penelitian menunjukkan bahwa rata-rata kecemasan matematika siswa yaitu 2,294. Kemampuan penalaran spasial siswa didominasi berada pada level sedang yakni 69,23%. Hasil penelitian juga menunjukkan bahwa kemampuan penalaran spasial siswa tidak bergantung pada kategori kecemasan matematika. Kemampuan orientasi spasial menjadi kemampuan yang paling banyak dikuasai siswa. Setelah kecemasan matematika dan kemampuan penalaran spasial siswa diketahui maka diharapkan dapat menjadi bahan pertimbangan guru dalam mendesain pembelajaran geometri di kelas yang dapat merangsang perkembangan penalaran spasial siswa, pun juga dapat mengurangi tingkat kecemasan matematika siswa.